Application of simulation techniques to optimize concentrate stockpile requirements of a copper smelter - J. G. Eacott; M. A. T. Cocquerel (Canadian Institute of Mining, Metallurgy and Petroleum, 1980)
"Simulation techniques may be used to optimize existing processes and plant operations, and in plant design at the engineering study stage of a project . This paper describes the latter application, using a computer, to optimize the concentrate stockpile requirements of a modern copper smelter.A large open-pit mining operation is envisaged and it is assumed that copper concentrate is smelted in two flash furnaces. The proposed mining plan gives rise to metaffurgical considerations in smelting which dictate that concentrate blending is carried out in the early years of operation in order to eliminate wide variations in the grade of concentrate charged to the furnaces . Stockpiling facilities are therefore necessary for blending purposes and also to provide a strategic reserve of concentrate to ensure continuity of concentrator and smelting operations.The objective of the study is to determine the optimum size of concentrate stockpile required to take account of both metaffurgical and strategic considerations. Two separate simulation models are developed to achieve this objective. The first model is used to determine the minimum size of stockpile necessary for blending purposes to smooth out variations in concentrate grade between 15 - 60% Cu, with associated 34 6% Fe, respectively, and ensure that the concentrate fed to the furnaces does not faff below 12% Fe, which is considered a minimum for good smeltability.The second simulation model covers a projected three-year operating period and indicates the maximum size of stockpile which is likely to develop during scheduled and unscheduled shutdown periods in the concentrator and smelter.Covered storage volume and conveying facilities for the optimum size of concentrate stockpile can be designed based on the results generated by the simulation models."